A New Engine Simulation Structure Model Applied to SI Engine Controlling - Nekooei, Mohammad Javad; Koto, J.; Ghani, M.Pauzi; Dehghani, Zahra (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
High ratio emissions that outcome from incomplete combustion cause air contamination, poorer the performance of the spark ignition (SI) engine and raise fuel consumption. Because of engine configurations, engine wrong adjustment and engine subsystems, unfortunately completed combustion is not possible with SI engines .As a result of uncompleted combustion a high ratio of CO, HC, NOX and PM harmful emissions such as come into atmosphere. Study has exposed that exact AFR control can successfully decrease emission of dangerous exhaust, such as CO, NOX and unburned HC. To achieved this goal we need to make a correct engine simulation structure which it can be used to controlling AFR. Firstly, the existing engine simulation models and structures will be studied in this paper, where benefits and disadvantages of several simulation models and structures kinds are discussed. After that we will present our new engine simulation structure model.